Citrus BMP Implementation in Florida’s Gulf Citrus Production Area: Pesticides - Sanjay Shukla; R.E. Rouse; S.S. Shukla; E.A. Hanlon; K. Portier; T.A. Obreza (EDIS)
This document is about a survey conducted to quantify the implementation of pesticide Best Management Practices (BMPs) in the Gulf Coast Production Area (GCPA) citrus industry. The survey results revealed that most pesticide BMPs are widely adopted, with 13 out of 19 BMPs practiced on at least 80% of the surveyed area. This high adoption rate underscores the growers' awareness of the environmental and health impacts of pesticide use and their commitment to mitigating these effects. Key BMPs, such as targeted pesticide spraying, measures to reduce spray drift, regular equipment inspections, and proper storage practices, are extensively implemented. An informative BMP manual has been developed, and ongoing education and cost-share programs are recommended to support continuous improvement and adaptation to new regulations. Future surveys are suggested to monitor progress and effectiveness of these initiatives. First published Aug. 2010.